Community characteristics and functional diversity of the rhizosphere microorganism and endophyte from Pinus dabeshanensis - XIANG Xiaoyan1, RUAN Sirui1, ZHANG Ying2, ZHAO Feifei2, XU Weifang2* (Guangxi Zhiwu)
Pinus dabeshanensis is an endangered plant. In order to explore the community characteristics and functional diversity of plant-associated microbes, the compositions of rhizosphere microbiota and root endophyte from P. dabeshanensis were analyzed based on the high-throughput sequencing technology. And the functions of bacterial and fungal communities were predicted by using PICRUSt and FUNGuild software, respectively. The results were as follows:(1)The rhizosphere soil samples exhibited higher operational taxonomic units(OTUs)and α-diversity indices than those of the root endophyte.(2)Rhizosphere microbiota were mainly composed of microflora such as Firmicutes(genus: Listeria), Proteobacteria(genus: Acetobacter), Ascomycetes(genus: Fusarium and Chaetomium)and so on, while root endophyte were mainly composed of Firmicutes(genus: Lactobacillus and Bacillus), Ascomycetes(genus: Cladosporium), and Basidiomycetes(genus: Pleurotus and Chaetomium).(3)The functional annotation results showed that the rhizosphere microbial community was prominent in cell mobility, environmental adaptability, and amino acid metabolism, etc., while the root endophyte community was prominent in enzyme family, digestive system, and energy metabolism, etc. Both rhizosphere fungal community and root endophytes contain symbiotic, saprophytic, pathophytic and cross-trophic fungal groups, and ectomycorrhiza were more abundant in root tissue. Collectively, there were differences in flora richness, community structure and functional diversity between rhizosphere microorganism and root endophyte of P. dabeshanensis. The study contributed to knowledge of the structure and function of rhizosphere microorganism and endophyte of P. dabeshanensis, and it provided a theoretical basis for the later development of potential microbial agents for use in promoting plant growth and controlling plant diseases.